Mitotic Catastrophe - Role in Programming of Cell Death - Prasanna Nichat1; Neha Mishra2; Richa Bansal3; Harshaminder Kaur4 (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2016)
The incidence of cancer worldwide is on a rise, accounting it to be the second most common disease, first being the coronary heart disease [1]. The losses of cellular regulation that gives rise to most or all cases of cancer are due to genetic damage. Mutations, in two broad classes of genes - proto-oncogenes (eg, ras) and tumor suppressor genes (eg, APC) - play key roles in cancer induction. These genes encode many kinds of proteins that help control cell growth and proliferation. All human tumors have inactivating mutations in genes that normally act at various cell-cycle checkpoints to stop a cell's progress through the cell cycle if a previous step has occurred incorrectly or if DNA has been damaged [2]. The cell cycle checkpoints or mitotic kinases are the rigorous quality control steps of mitosis [3] that function in preserving the fidelity and integrity of DNA and allow mitosis to continue with accurately functioning DNA, spindle assembly, centrosome and kinetochore thus preventing cell death through mitotic catastrophe [4]. Most cancer cells are deficient in G1 checkpoint function and therefore fail to arrest in G1 phase on exposure to genotoxic agents. Instead, they accumulate temporarily in G2 phase. However, given that the G2 checkpoint is also partially impaired in cancer cells, they are unable to maintain G2 arrest and eventually die as they enter mitosis. This process is known as mitotic catastrophe or mitotic death [5].